2018
DOI: 10.3390/bs8020022
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Social Contingency in Adults with High-Functioning Autism during Computer-Mediated Embodied Interaction

Abstract: Autism Spectrum Disorder (ASD) can be understood as a social interaction disorder. This makes the emerging “second-person approach” to social cognition a more promising framework for studying ASD than classical approaches focusing on mindreading capacities in detached, observer-based arrangements. According to the second-person approach, embodied, perceptual, and embedded or interactive capabilities are also required for understanding others, and these are hypothesized to be compromised in ASD. We therefore re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Our findings in random pairs from the general population showed that time spent together did not change per round, indicating that participants kept exploring the space rather than increasingly staying with the other avatar. In contrast, Zapata-Fonseca et al (2018) found controls to decrease their exploring behavior in interaction with individuals with autism spectrum disorder. This may also be explained by the difference in age, with an adult population more easily reaching a decision and sticking to what they think is the other person.…”
Section: Comparison With Previous Findingsmentioning
confidence: 78%
See 3 more Smart Citations
“…Our findings in random pairs from the general population showed that time spent together did not change per round, indicating that participants kept exploring the space rather than increasingly staying with the other avatar. In contrast, Zapata-Fonseca et al (2018) found controls to decrease their exploring behavior in interaction with individuals with autism spectrum disorder. This may also be explained by the difference in age, with an adult population more easily reaching a decision and sticking to what they think is the other person.…”
Section: Comparison With Previous Findingsmentioning
confidence: 78%
“…Indeed, our correct detection rate in adolescents was lower compared with adults. Further, Zapata-Fonseca et al (2018) have shown that click correctness did not distinguish participants with high functioning autism from controls, while interaction patterns differed. Potential ambiguity in the interpretation of quantitative findings could be solved by including a qualitative aspect and comparing this with the quantitative findings (Froese et al, 2014).…”
Section: Future Considerations Regarding Methodologymentioning
confidence: 94%
See 2 more Smart Citations
“…In the study by Landa et al, toddlers with ASD were randomized to either a classroom-based inter-personal synchrony intervention (including imitation, joint attention, and affect sharing) or a non-inter-personal synchrony intervention. It was found that after approximately 200 hours of interpersonal synchrony interventions (versus non-interpersonal synchrony interventions), toddlers showed enhanced socially engaged imitations paired with eye contact with the examiner and demonstrated a trend toward higher levels of nonverbal cognition during posttest assessments (90). The study provided evidence for plasticity in these developmental systems in toddlers with ASD.…”
Section: Manipulation Of Inter-personal Body Synchronymentioning
confidence: 80%